2009
DOI: 10.1080/03014460902839194
|View full text |Cite
|
Sign up to set email alerts
|

Culture in psychiatric epidemiology: Using ethnography and multiple mediator models to assess the relationship of caste with depression and anxiety in Nepal

Abstract: Background The causes of ethnic and caste-based disparities in mental health are poorly understood. Aim To identify mediators underlying caste-based disparities in mental health in Nepal. Subjects and methods A mixed methods ethnographic and epidemiological study of 307 adults (Dalit/Nepali, n=75; high caste Brahman and Chhetri, n=232) assessed with Nepali versions of Beck Depression (BDI) and Anxiety (BAI) Inventories. Results One third (33.7%) of participants were classified as depressed: Dalit/Nepali … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 32 publications
10
109
2
Order By: Relevance
“…Study done by Banerjee et al also reported that schizophrenia is commonly found among Dalit patients. Similar findings were reported in the research conducted in the Rural Community of Nepal as well 1,17 . It is because Nepal is an under developed country having poor financial status which could lead to high prevalence of psychiatric illness.…”
Section: Socio-economic Demographic Factors and Psychiatric Disorderssupporting
confidence: 79%
See 2 more Smart Citations
“…Study done by Banerjee et al also reported that schizophrenia is commonly found among Dalit patients. Similar findings were reported in the research conducted in the Rural Community of Nepal as well 1,17 . It is because Nepal is an under developed country having poor financial status which could lead to high prevalence of psychiatric illness.…”
Section: Socio-economic Demographic Factors and Psychiatric Disorderssupporting
confidence: 79%
“…Many Nepalese people are financially poor and therefore can't afford to have health care facility timely and in course of time it may result in various psychiatric disorders. A research conducted in Nepal by Kohrt BA et al also concluded that the caste-based disparity, poverty, lack of social support and stressful life events have adversely affected the mental health of Nepalese people 1 .…”
Section: Socio-economic Demographic Factors and Psychiatric Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, other studies have found that increasing age is a predictor of depression among hypertensive Section: Medicine patients. [24][25][26] In the other hand, In Nigeria, a study had found no significant correlation between age and incidence of depression among patients attending the hypertensive clinic. Women hypertensive patients were found to experience depression at a higher rate than men in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 21-item BDI-Ia, Nepali version [37,38], was used to assess depression in participants over the prior 2 weeks (Cronbach's alpha = 0.89). Items are scored on a four-point Likert scale with an instrument range of 0 to 62.…”
Section: Methodsmentioning
confidence: 99%